Ecological aspects of Aglaoctenus lagotis (Araneae: Lycosidae) with emphasis in preference of habitat. Corrientes, Argentina - RUBIO, GONZALO D.; MEZA-T., ESTEBAN I.; ÁVALOS, GILBERTO (Revista Colombiana de Entomología, 2005)
Some ecological aspects of Aglaoctenus lagotis Holmberg such as its presence in the plant species Aechmea distichantha Lem. and Bromelia serra Lem. (Bromeliaceae) were studied. The study was carried out in the Laguna Brava locality, Corrientes province, Argentina. The banded and record method was utilized through two transects 300m long each. 162 individuals were recorded from 650 bromeliads observed. Both, the two proportions test and the choice test indicated a strong preference of the spiders for the individuals of A. distichantha located in the forest and under low sunlight exposition. 38,2% of the individuals of A. distichantha and 4,3% of individuals of B. serra were inhabited by A. lagotis respectively. It is necessary to conduct comparative studies in different localities in order to check the presence of this psider in other Bromeliad species such as Vriesea, Billbergia y Pseudananas.